2021
DOI: 10.1038/s41396-021-00929-7
|View full text |Cite
|
Sign up to set email alerts
|

Human-associated microbiota suppress invading bacteria even under disruption by antibiotics

Abstract: In light of their adverse impacts on resident microbial communities, it is widely predicted that broad-spectrum antibiotics can promote the spread of resistance by releasing resistant strains from competition with other strains and species. We investigated the competitive suppression of a resistant strain of Escherichia coli inoculated into human-associated communities in the presence and absence of the broad and narrow spectrum antibiotics rifampicin and polymyxin B, respectively. We found strong evidence of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Recently, significant focus has turned to the resistome and the relationship between the complex microbiome and its interaction with pathogen behavior, and whether the overall resistance of mixtures of bacteria found in the site of infection might affect the effectiveness of antibiotic treatment [13,30]. In this study, we explore the possibility of an alternative approach to the phenotype-based method that determines the MIC value directly from mixed bacterial population in a sample [3,9,31]. Whilst this may not provide the same standardized measure of antibiotic susceptibility of each individual strain present in the sample, it will be important to continue researching the link between "mixed MIC" found from direct susceptibility testing Our assay is simpler than many microfluidic devices, and the open source 3D-printed frame design is flexible and customizable.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, significant focus has turned to the resistome and the relationship between the complex microbiome and its interaction with pathogen behavior, and whether the overall resistance of mixtures of bacteria found in the site of infection might affect the effectiveness of antibiotic treatment [13,30]. In this study, we explore the possibility of an alternative approach to the phenotype-based method that determines the MIC value directly from mixed bacterial population in a sample [3,9,31]. Whilst this may not provide the same standardized measure of antibiotic susceptibility of each individual strain present in the sample, it will be important to continue researching the link between "mixed MIC" found from direct susceptibility testing Our assay is simpler than many microfluidic devices, and the open source 3D-printed frame design is flexible and customizable.…”
Section: Discussionmentioning
confidence: 99%
“…Although ampicillin and E.coli are undoubtedly of high real-world relevance, generalizing our results to other species/antibiotics should be done with caution. A recent study by Letten et al [ 48 ] with a similar setup, but different antibiotics, samples and focal strain, found little evidence that antibiotics released an invading strain from competition with resident microbiota. This difference may be explained by different antibiotics having different effects on resident microbiota, variation among focal resistant strains, or other differences between experiments (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be explained by different antibiotics having different effects on resident microbiota, variation among focal resistant strains, or other differences between experiments (e.g. baseline competition with resident microbiota was relatively strong in Letten et al [ 48 ]). Conversely, a past experiment also using this study system showed an ampicillin-resistance plasmid conferred a relatively large fitness benefit to its host when embedded in a gut microbiota and exposed to ampicillin [ 16 ], consistent with our results here.…”
Section: Discussionmentioning
confidence: 99%
“…the manner in which host population structures and host resistance drive parasite spread and make parasite control feasible beyond a limited range of targeted host individuals. Moving beyond this, incorporation of systematic monitoring and understanding the movement of drug resistant genomes within the parasite population (Ndiaye et al 2021 ) and the invasion success of drug resistant parasite in host microbial and parasite assemblages (Letten et al 2021 ) will be key for informed drug use in parasite control. The advent of affordable and fast in-field genomic technologies makes this approach more feasible.…”
Section: Introductionmentioning
confidence: 99%